2012
DOI: 10.1086/668023
|View full text |Cite
|
Sign up to set email alerts
|

Hospital-Onset Clostridium difficile Infection Rates in Persons with Cancer or Hematopoietic Stem Cell Transplant: A C3IC Network Report

Abstract: A multicenter survey of 11 cancer centers was performed to determine the rate of hospital-onset Clostridium difficile infection (HO-CDI) and surveillance practices. Pooled rates of HO-CDI in patients with cancer were twice the rates reported for all US patients (15.8 vs 7.4 per 10,000 patient-days). Rates were elevated regardless of diagnostic test used.In 2011, an estimated 1.6 million people underwent treatment for cancer. 1 Clostridium difficile is the most common bacterial cause of healthcare-associated di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
56
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 8 publications
3
56
0
Order By: Relevance
“…Allogeneic HSCT recipients are among the most susceptible hosts for CDI (1, 3, 12, 15). Our study demonstrates that most CDIs occur around the time of conditioning and in the first week following stem cell infusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Allogeneic HSCT recipients are among the most susceptible hosts for CDI (1, 3, 12, 15). Our study demonstrates that most CDIs occur around the time of conditioning and in the first week following stem cell infusion.…”
Section: Discussionmentioning
confidence: 99%
“…When used for diagnosis of CDI, molecular methods offer many advantages over widely used enzyme immunoassay (EIA) and cytotoxin neutralization assays, including higher sensitivity and rapid turnaround time, detection of colonization is much higher with these assays that detect the toxin gene. With doubling of C. difficile detection rates reported by many centers after implementation of PCR(3, 23), interpretation of a positive test in this population will have to be carefully evaluated in prospective studies that employ screening strategies and rigorously implemented clinical scoring systems to overcome the diagnostic challenge of distinguishing between active infection and colonization(3). …”
Section: Discussionmentioning
confidence: 99%
“…The current body of literature suggests that rates of CDI among patients with cancer are more than twice the rates reported for all hospitalized patients in the US [21]. Among auto HSCT recipients, these rates have ranged between 5-15% [9,10,22-24], with most infections occurring in the first 30 days of HSCT [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Cancer chemotherapy has been associated with CDI through its damaging effects to the intestinal mucosa and the alterations it causes to the gut microbiota [34,35]. A recent multicenter survey of 11 US cancer centers demonstrated that the pooled rate of hospital-onset CDI in patients with solid and hematological malignancies was 15.8 per 10,000 patient-days, twice the rate reported for all US patients [36]. In another large single center study, hematological malignancy was identified as an independent risk factor for CDI [37].…”
Section: Epidemiologymentioning
confidence: 99%
“…HSCT recipients are a severely immunosuppressed group of patients with the highest reported rates of CDI amongst those suffering of malignancy [36]. A US study of 999 autologous and allogeneic HSCT recipients found that CDI was common in the early post-transplant period with a 1-year incidence of 9.2% [28].…”
Section: Epidemiologymentioning
confidence: 99%